Metabolic bone disease of prematurity: discerning calcium versus phosphorus deficiency and role of calcitriol in its management - Lee, Yee Lin; Abu Hassan, Hasyma; Vasanwala, Rashida Farhad (Sage Publications, 2022)
Introduction: Metabolic bone disease of prematurity (MBDP) is prevalent among preterm infants despite major advances in neonatal care. Initial and ongoing assessment of complete bone metabolic markers help direct correct therapeutic mineral replacement. Case Presentation: A preterm infant of 30 weeks gestation and birth weight 1 kg sustained multiple spontaneous metaphyseal fractures at 5 months of age. The infant had multiple comorbidities including perforated necrotizing enterocolitis, chronic lung disease, short gut syndrome, and total parenteral nutrition-related cholestasis. Initial metabolic bone profile showed a rising trend of alkaline phosphatase (ALP) with normal calcium and declining phosphorus levels despite ongoing phosphorus supplements. Further workup showed elevated parathyroid hormone (PTH), low tubular reabsorption of phosphate (TRP), and low 25-hydroxyvitamin D (25(OH)D) levels, suggesting calcium/vitamin D deficiency with secondary hyperparathyroidism rather than inadequate phosphorus intake. Calcium and vitamin D supplementation were commenced and optimized, resulting in a decline in PTH, but ALP remained elevated. Treatment with calcitriol at dose range of 0.07 mcg/kg/day to 0.12 mcg/kg/day for 4.5 months duration led to a fall in ALP and PTH to near normal levels. Conclusion: Early nutrition with focus on calcium, phosphorus, and vitamin D is crucial to prevent MBDP. MBDP assessment should include serum PTH, TRP, and 25(OH)D levels to determine the specific mineral deficiency so that calcium, phosphorus, or vitamin D can be supplemented appropriately. Calcitriol is an effective treatment modality for calcipenic rickets where targeted mineral supplementation has been optimized.